Long-term Mortality Risk and Life Expectancy Following Recurrent Hypertensive Disease of Pregnancy. Issue 1 (March 2019) - Theilen, L.H.; Meeks, H.; Fraser, A.; Esplin, M.S.; Smith, K.R.; Varner, M.W.
Abstract : ( Am J Obstet Gynecol . 2018;219:107.e1–e6) Hypertensive disease of pregnancy has been associated with early mortality from cardiovascular disease. However, there is currently no data available on the relationship between recurrent pregnancies complicated by any hypertensive disease of pregnancy and all-cause mortality in the United States. This study aims to bridge this knowledge gap and compare the risk of early mortality between women with recurrent hypertensive disease of pregnancy and women with 0 affected pregnancies or 1 affected pregnancy.